Distraction Modulates Self-Referential Effects in the Processing of Monetary and Social Rewards - Zhu, Jia; Zhan, Youlong (Frontiers in Psychology, 2019)
A reward that is personally relevant tends to induce stronger pursuit motivation than a reward that is linked to other people. However, the role of attention in eliciting this “self-referential reward effect” remains unclear. In our two studies, we evaluated the significance of attention in self-referential reward processing utilizing an ownership paradigm, which required participants to complete a visual search task to win either monetary rewards (in Study 1) or social rewards (in Study 2) for themselves or for an acquaintance. Access to attentional resources was manipulated by sometimes including a distracting stimulus among the presented stimuli. The results of Study 1 revealed that a significant self-referential reward effect emerged under undistracted attentional conditions and was associated with improved task performance when self-owned monetary rewards were available. However, distracted attention impaired this self-referential reward effect. Moreover, distracted attention was also observed in the self-referential social reward processing in Study 2. These results suggested that distracted attention can impair the pursuit advantage for self-relevant rewards; self-referential processing is strongly dependent on attentional resources.